International Auditing Standards and their role in rationalizing the auditor's personal judgment in Iraq" - ابراهيم, لبنى زيد; عبد الرحمن, دعاء محمد (Journal of Economics and Administrative Sciences, 2018)
The impact of the auditor's personal judgment starts from the beginning of the audit process to the formation of the final opinion and the issuance of the report, and because of the possibility of bias in the auditor's judgment for various reasons that may relate to the auditor himself or the circumstances surrounding it, which requires assessing the current reality of the auditor's personal judgments In the local environment and determining their determinations. To clarify the concept and determinants of the auditor's personal judgments when implementing the audit work, prepare the report and determine the role of the international auditing standards in rationalizing the auditor's personal judgment when conducting his audit activity. Implementing the requirements of international auditing standards that require the exercise of personal judgment, which helps the auditor in rationalizing and limiting his personal provisions .But , there are some shortcomings that may be reflected in the auditor's judgment, including the auditor's reliance on his personal experience only in determining the relative importance of the component, as well as the auditor's greater reliance on the internal audit evidence, as well as the fact that the auditor does not use analytical procedures at the end of the process The audit is in the preparation stage of the report, which is a basic requirement of the audit standard 520, which is reflected in the personal judgments taken. The study concluded with a set of recommendations, the most important of which is the need to carry out training activities related to personal judgment and to raise awareness and confidence in it to enhance the expertise of the auditors and the auditor to collect more relevant internal and external information before taking personal judgment as well as guidelines and instructions to improve the ability to exercise personal judgment. With regard to carrying out analytical procedures near the end of the audit process, and relying more on external audit evidence.